A Mandarin/English two‐way immersion program: Language proficiency and academic achievement. (20th November 2013) - Padilla, Amado M.; Fan, Lorraine; Xu, Xiaoqiu; Silva, Duarte
Abstract A Mandarin/English two‐way immersion elementary program is described from its inception and implementation through the fifth grade, the culminating year of the program. All students in all grades were assessed on their oral/listening, reading, and writing performance in Mandarin using program‐created assessment measures. Fifth‐grade students also took the Mandarin STAMP 4Se test online to assess their oral and literacy performance. In addition, all second‐ through fifth‐grade students participated in the mandated California Standards Tests for English language arts, writing (fourth grade), math, and science (fifth grade). Results showed that across grades, Mandarin immersion students acquired high‐level performance in oral/listening, reading, and writing in Mandarin. A comparison of Mandarin heritage students with non‐heritage students in the immersion program initially favored heritage students in the acquisition of Mandarin; however, this advantage was not statistically significant in the later grades. On the mandated California standardized tests, the non‐immersion students from the same school in the second and third grades had higher scores on the English language arts and math test, but in the upper grades, Mandarin immersion students scored higher than their non‐immersion peers in these two subject areas.